Performance Comparison of H2O and CO2 as the Working Fluid in Coupled Wellbore/Reservoir Systems for Geothermal Heat Extraction - Lei, Hongwu (Frontiers in Earth Science, 2022)
CO2 is considered as a novel heat-transmission fluid for extracting geothermal energy from enhanced geothermal systems (EGS), attributed to its high compressibility, expansivity and low viscosity in comparison to water. In order to compare the performance of CO2 and H2O as the working fluid in EGS, a classical five-spot model based on the geologic and geothermal conditions at the Songliao Basin, China, was constructed. Results obtained from the coupled wellbore/reservoir model revealed that the net heat extraction and flow rate are greater for CO2 than for H2O at a fixed operation pressure difference between the injection and production wellheads. However, the wellhead temperature is far lower for CO2 than for H2O due to the strong Joule–Thomson effect of CO2 in the wellbore. Moreover, a stronger pressure change in the wellbore is observed by using CO2, attributed to the gravity and high flow velocity of CO2; this pressure change induces a drop in the frictional pressure. For CO2, the enthalpy change in the wellbore is mainly contributed by the gravitational potential, while for H2O, it is contributed by the gravitational potential and lateral heat exchange. The heat extraction performance depends on the operation pressure difference and injection temperature for H2O-based EGS, while it depends on the wellhead pressures of both the injection and production wells as well as the injection temperature for CO2-based EGS. A high operation pressure is favorable for improving the heat extraction performance (especially the production temperature) for CO2. With the temperature drop limitation at the downhole of the production well, the heat extraction performance is better by using H2O than that by using CO2 as the working fluid. However, the low-power consumption for maintaining fluid circulation demonstrates the application potential of CO2-based EGS.